Liberation Theology and Theology of Integral Mission: history, emphasis and differences - Oliveira Borges, Letícia (Vox Scripturae - Revista Teológica Internacional, 2014)
Would the Theology of Integral Mission be a mirror of the Liberation Theology? Many believe that the Theology of Integral Mission is an evangelical interpretation of the Liberation Theology, however, throughout this essay, the main differences between the two theologies, from a brief rescue of its origins and some of its distinctive precepts, will be delineated. The approach arrives at the result that they are two distinct types of theology, even though there is certain proximity.
Keywords: Integral Mission; Liberation Theology